Chemokines in cardiovascular risk prediction - Aukrust, Pål; Yndestad, Arne; Smith, Camilla; Ueland, Thor; Gullesta, Lars; Damås, Jan K. (Thrombosis and Haemostasis, 2007)
In consideration of the important role of inflammation in plaque progression and stability, recent work has focused on whether plasma markers of inflammation can non-invasively diagnose and predict coronary artery disease (CAD) and other forms of atherosclerotic disorders. Although several studies support an important pathogenic role of chemokines in atherogenesis and plaque destabilization, potentially representing attractive therapeutic targets in atherosclerotic disorders,this does not necessarily mean that chemokines are suitable parameters for risk prediction. In fact, the ability to reflect up-stream inflammatory activity, stable levels in individuals and high stability of the actual protein (e.g. long half-life and negligible circadian variation), are additional important criteria for an ideal biomarker in cardiovascular disease. Although plasma/serum levels of certain chemokines (e.g. interleukin 8 and monocyte chemoattractant protein- 1) have been shown to be predictive for future cardiac events in some studies, independent of traditional cardiovascular risk factors and C-reactive protein,and although certain gene polymorphisms of chemokines/chemokine receptors (e.g. fractalkine receptor) have been shown to be predictive of future atherosclerotic disease, further prospective studies, including a larger number patients,are needed to make any firm conclusion. While the demonstrations of an association between chemokines and CAD are a necessary first step, such studies do not establish the full clinical utility of a biomarker, which is a more demanding process that requires validation in multiple cohorts, and clear demonstration of incremental prognostic value over traditional risk models. If successful, such new biomarker will be a useful indicator for better risk assessment,diagnosis,and prognosis, as well as monitoring pharmacological treatments for atherosclerosis.
Keywords: Chemokines; atherosclerosis; gene polymorphism; biomarkers; inflammation